DEVELOPMENT OF INSURANCE INTERMEDIARIES IN THE DEVELOP EUROPEAN COUNTRIES - D. Nesterova; N. Kudriavska (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article presents theoretical and practical approaches in determining the features of insurance intermediation. It characterizes the traditional model of selling insurance products and modern multi-channel sales model of insurance services. It identifies the main legal acts that regulate the activities of insurance intermediaries in the European Union. In the article analyzed the activity of insurance intermediaries in the EU. The main channels of sales of insurance products are determined. The shares of premiums of insurance intermediaries in the volume of insurance premiums and in the GDP of the insurance markets of European countries are defined. The number of employees who are involved in insurance intermediary in the European countries is investigated. The European experience of insurance agents and insurance brokers in non-life insurance and life insurance is considered. It's analyzed the activity of insurance brokers in the Ukraine. The main trends and problems of the development of insurance intermediaries in the insurance market of Ukraine are defined.